Effect of sodium dodecyl sulfate on solution behavior of thermoresponsive polymers and their mixtures - Otulakowski, Lukasz; Kasprow, Maciej; Dworak, Andrzej; Trzebicka, Barbara (Polimery, 2021)
The process of thermal aggregation in water of thermoresponsive (co)polymers poly(N-isopropylacrylamide) PNIPAM, poly{[di(ethylene glycol) monomethyl ether methacrylate]-co-[oligo(ethylene glycol) monomethyl ether methacrylate]} P(D-co-O300), the bioconjugate of P(D-co-O300) with the peptide metenkephalin (MetDns) and their mixtures was investigated. The effect of the SDS (sodium dodecyl sulfate) addition on the behavior of thermoresponsive chains was evaluated by UV-Vis (ultraviolet-visible spectroscopy) and DLS (dynamic light scattering) methods. It was found that the presence of SDS influences the polymer transition temperature. It also reduces the size of the aggregates, which explains the higher transmittance value of the solution above phase transition.